2011
DOI: 10.1093/fampra/cmq105
|View full text |Cite
|
Sign up to set email alerts
|

Family doctors' views of pharmaceutical sales representatives: assessment scale development

Abstract: FDs evaluate PSRs mainly by their managerial skills and trustworthiness. The scale proved to be a reliable tool for assessing PSRs by FDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
3
11
0
1
Order By: Relevance
“…Sense of trustworthiness is a group of PSRs’ characteristics that Slovenian FPs value the most and selling skills is the group that they value the least. Trustworthiness was recognized as the most valuable set of characteristics also in our previous study (13) and in some foreign studies (6, 12). Also, selling skills were recognized less important, same as in our previous study (13).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Sense of trustworthiness is a group of PSRs’ characteristics that Slovenian FPs value the most and selling skills is the group that they value the least. Trustworthiness was recognized as the most valuable set of characteristics also in our previous study (13) and in some foreign studies (6, 12). Also, selling skills were recognized less important, same as in our previous study (13).…”
Section: Discussionsupporting
confidence: 56%
“…We inserted a letter of invitation from the president of Slovenian Family Medicine Society and a questionnaire. It consisted of a previously validated PSRs’ assessment scale (13). This scale consists of 12 questions on PSRs’ assessment that could be answered on a seven-point Likert scale (ranges from 1 – not important to 7 – very important).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chressanthis et al [16] determined that, given the limited access to physicians, MRs tend to focus on areas where they can have the greatest impact on sales, while others have contended that brand prescriptions add to the cost of care with little or no added value [17]. Janko and colleagues [18] further found that family physicians appreciate the scientific content and objectivity of information provided by MRs. Although aggressive marketing of pharmaceuticals can cause doctors to prescribe medicines on the basis of information about other scientific evidence, more than 75% of physicians found MRs’ visits to be valuable in learning about new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Literatürde yapılan çalışmalarda, kişisel satışın hekimlerin reçeteleme kararlarına pozitif etkileri olduğu (Ashker ve Burkiewicz, 2007;Brett ve diğ., 2003); reçeteme davranışlarının hekimlerin tutumlarına, sübjektif normlarına ve kişisel deneyimlerine bağlı olarak değiştiği sonucu bulunmuştur (Feely ve diğ., 1999;Kersnik ve diğ., 2011) Bilginer ve arkadaşları (2004) 135 ilaç mümessilleri ile gerçekleştirdikleri çalışmalarında ilaç mümesillerinin %71'i hekimlerin reçete yazma eğilimi analiz edebildiklerini ifade etmişlerdir. Mümessillerin %46'si ilacın eş değerinin bulunmaması, %30'u ilacın etkinliği, %29'u ilaç mümessilinin ziyaretinin sıklığı, %28'i ilaç mümessilleri ile olan iyi ikili ilişkilerine göre hekimlerin reçeteleme eğilimi içinde olduklarını belirtmişlerdir.…”
Section: Introductionunclassified